Nanoisozymes: The Origin behind Pristine CeO2 as Enzyme Mimetics. Issue 46 (23rd July 2020) - Tan, Zicong; Chen, Yu‐Cheng; Zhang, Jieru; Chou, Jyh‐Pin; Hu, Alice; Peng, Yung‐Kang
Abstract: It is known that the interplay between molecules and active sites on the topmost surface of a solid catalyst determines its activity in heterogeneous catalysis. The electron density of the active site is believed to affect both adsorption and activation of reactant molecules at the surface. Unfortunately, commercial X‐ray photoelectron spectroscopy, which is often adopted for such characterization, is not sensitive enough to analyze the topmost surface of a catalyst. Most researchers fail to acknowledge this point during their catalytic correlation, leading to different interpretations in the literature in recent decades. Recent studies on pristine Cu2 O [ Nat. Catal . 2019, 2, 889; Nat. Energy 2019, 4, 957] have clearly suggested that the electron density of surface Cu is facet dependent and plays a key role in CO2 reduction. Herein, it is shown that pristine CeO2 can reach 2506/1133 % increase in phosphatase‐/peroxidase‐like activity if the exposed surface is wisely selected. By using NMR spectroscopy with a surface probe, the electron density of the surface Ce (i.e., the active site) is found to be facet dependent and the key factor dictating their enzyme‐mimicking activities. Most importantly, the surface area of the CeO2 morphologies is demonstrated to become a factor only if surface Ce can activate the adsorbed reactant molecules. Abstract : Surface activity : The electron density of surface Ce is revealed to be facet dependent among CeO2 morphologies, in the order of cubes (100) > rods (110) > octahedra (111), which significantly affects their enzyme‐mimicking activities. For pristine CeO2 with Ce atoms on the (111) surface of octahedra, lower electron density can facilitate its phosphatase‐like activity, whereas their counterparts on the (100) surface of cubes are the key for high peroxidase‐like activity.